Effect of long time exposure on the chemical and physical properties of polyvinyl chloride/titanium dioxide nanocomposites. (November 2016) - Mehmandoust, Shadi Ghaebi; Sokhandani, Parvane; Abdi, Mohammad Adel; Babaluo, Ali Akbar; Alizadeh, Reza
The photodegradation behavior of poly(vinyl chloride) (PVC) nanocomposites containing different amounts of synthesized titanium dioxide (TiO2 ) nanoparticles and commercial rutile powder is investigated via the formation of carbonyl compounds, peroxides, and polyenes propagation over 5112 h exposure, as a function of irradiation wavelength and intensity. All the PVC/TiO2 nanocomposites are found to exhibit lower concentration of mentioned species compared with the composite samples. The results show that added TiO2 nanoparticles can retard the photodegradation processes, wherein increasing the amounts of these nanoparticles yields more reduction. With an increase in irradiation intensity the rate of formation of investigated groups increases, although in cases with raised temperature range, this pattern is not observed. An evaluation on the irradiation wavelength effect also shows that more photon energy provides more degradation. The loss of weight analysis shows a tremendous and novel result on evaluating a point of meaningful weight loss.